Analysis of Nurse Personal Factors of Triage Decision-Making in Emergency Installation at University of Muhammadiyah Malang Hospital - Ali Rahmanto; Loeki Enggar Fitri; Ika Setyo Rini (Indian Journal of Forensic Medicine & Toxicology, 2021)
The high frequency of patient visits to the ER will disrupt the service process at the Emergency Department(IGD). One solution is the application of a triage system, which is the process of sorting patients accordingto their level of gravity. The accuracy of triage decisions has a significant impact on patient outcomes sothat in this case nurses in the ER must have knowledge, understanding, and skills about triage. Analyzepersonal factors that influence emergency nurse decision-making. This study aimed to identify personalfactors influencing triage decision-making among emergency nurses. Respondents were 30 male and femalenurses who worked and were active up to now in the IGD Hospital of the University of MuhammadiyahMalang. Data on work experience, education, and training were taken from data on the characteristics ofrespondents. The knowledge questionnaire came from the Emergency nurses association/ENA while theskills questionnaire used the Triage Skill Questionnaire/TSQ. The Spearman correlation test shows that thereis a significant relationship between skills and education with triage decision making (p=0.000; r=0.626 andp=0.039; r=0.378). Meanwhile, the variables of knowledge, work experience, and training do not correlatewith triage decision making (p> 0.05) except that GELS training shows a significant relationship betweenGELS training and triage decision making (p=0.016; r=0.437). The results of linear regression analysis,skills, and education are factors that influence decision-making in conducting triage in the ER (45,4%).Skills and education are the factors that most influence triage decision-making.